Rhizosphere engineering - Dubey, Ramesh Chandra; Kumar, Pankaj (Academic Press, 2022)
"Rhizosphere Engineering is a guide to applying environmentally sound agronomic practices to improve crop yield while also protecting soil resources. Focusing on the potential and positive impacts of appropriate practices, the book includes the use of beneficial microbes, nanotechnology and metagenomics. Developing and applying techniques that not only enhance yield, but also restore the quality of soil and water using beneficial microbes such as Bacillus, Pseudomonas, vesicular-arbuscular mycorrhiza (VAM) fungi and others are covered, along with new information on utilizing nanotechnology, quorum sensing and other technologies to further advance the science."--